KRITIK TERHADAP KLAIM KEANDALAN PADA HIRARKI PENGUKURAN NILAI WAJAR: Sebuah Literature Review - Nugroho Wisnu Murti; Indriyana Widyastuti (Akademi Akuntansi YKPN Yogyakarta, 2018)
This article provide consideration for the Indonesian Financial Accounting Standards Board that requires a review of Indonesia's Financial Accounting Standards (PSAK) 68 concerning Measurement of Fair Value. Fair Value has potential misinterpretation definition between price and value. This potential misinterpretation is indicated to be the rationale put forward in the fair value hierarchy which is indicated unfair. This potential based on claims at each level which can be questioned with the existence of aggressive discretionary issues and the analogy of financial statement analysis. However, this problem had been proven getting down by involvement of independent and professional assessment. Therefore, fair value hierarchy has the same potential of reliability by the third party. If each level has the same potential, this hierarchy can be removed to avoid misinterpretation by users of financial statements. The obligation to disclose the basis of valuation is fairer to be implemented than the hierarchy which is have potensial misinterpretation. This opinion was not without foundation, because this article based on a literature review that starts from: 1) study of the relevance of the Indonesian Financial Accounting Standards concerning fair value with the Indonesian Assessment Standards; 2) fundamental study to interpret fair value based on review literature; and 3) study of allegations of the same potential submitted in the direction of fair value as regulated in PSAK 68. Keywords: fair value hierarchy, riliability, agresive discretionary, PSAK 68